Prevalence of dysmenorrhea among reproductive age group in Saudi Women - Hanadi Bakhsh; Eatedal Algenaimi; Raghad Aldhuwayhi; Maha AboWadaan (BMC, 2022)
Abstract Background The condition of recurrent, crampy, lower abdominal pain during menses is defined as dysmenorrhea. The study aims to assess the factors affecting the prevalence of primary and secondary dysmenorrhea among Saudi women from the reproductive age group. Methods A cross-sectional survey-based study recruited 1199 participants through a systematic random sampling technique. The study was carried out among the reproductive age group in Saudi women (total number of 1199) who are more than 18-year-old and less than 45-year-old in Riyadh, King Dom of Saudi Arabia, using an electronic questionnaire. Results The observed dysmenorrhea in the study; 1107 (92.3%) women had non-pathological dysmenorrhea (primary) while 92 (7.7%) women had pathological dysmenorrhea (secondary) respectively. Conclusion In the present study, the prevalence of dysmenorrhea was high among the recruited Saudi women. The study suggests the inclusion of health education programs for students at the school and university level to deal with problems associated with dysmenorrhea that limit their interference with the student's life.